Artificial intelligence in administrative decision making / Mimi Sofiah Ahmad Mustafa - Ahmad Mustafa, Mimi Sofiah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Administrators in Malaysia are a class of people who are responsible to carry out the executive function to complement the legislative function (Parliament) and the judiciary function (courts). Administrators or executives play the role of implementing the laws passed by the Parliament in their day-to-day activities. UiTM, as an example, has its own power to do things that are allowed by the legislation to execute necessary duties and responsibilities to function as a higher learning institution. Other examples include immigration, the police, or the tax department which have their own tasks according to the respective laws. Decision making has always been an important task for an administrator. This power is conferred upon them through legislation so that they can solve issues relating to their daily internal functions according to the suitability of their organization. Hence, we can see from reports that one decision of an administrator could be different from another on the same issue. In internal inquiry involving staff disciplinary matters, for example, different interpretations could be made of how a decision could be reached. Where the law is concerned, the court will look at whether the administrators have followed the required procedure in reaching any decision. If it is not observed, then the court will likely rule that the administrator concerned has violated the law.